Strategic Study on Banking Credit Distribution Policy to Support the Sustainable Energy Sector for Achieving Community Welfare - Redy Rahmad Samosir; Abdullah Sulaiman; Megawati Barthos (Riviera Publishing, 2024)
This research aims to analyze bank lending policy strategies that support the sustainable energy sector in Indonesia, with a focus on improving the effectiveness of public welfare. The research identifies the urgency of sustainable energy as a response to global environmental challenges and the need for sustainable development. With reference to Law No. 23/1999 on Bank Indonesia and Bank Indonesia Regulation No. 14/22/PBI/2012, the normative juridical method was used to analyze the relevant legal and policy frameworks, as well as lending practices by banks in Indonesia. The results revealed a gap between existing policies and the implementation of lending practices, especially in relation to sustainable energy projects. The analysis highlights the need for capacity building of banks in managing sustainable energy project risks, development of innovative financing products, and cross-sector collaboration. The research shows that transparency and adequate reporting standards can increase trust and attract more investment into sustainable energy projects. The results confirm that the suggested strategies can enhance the role of banks in supporting Indonesia's transition to sustainable energy and contribute to people's welfare. The implications of this research emphasize the importance of implementing the research recommendations to strengthen synergies between bank lending policies and sustainable energy initiatives in Indonesia.